Therapeutic effort limitation a none very lucky term / Limitación del esfuerzo terapéutico un término poco afortunado - Betancourt Reyes, Gilberto Lázaro (Revista Cubana de Medicina Intensiva y Emergencias, 2017)
In the last decades, the gigantic scientific-technological progress in the medical sciences, it has represented an extraordinary possibility of progress to the healthcare of the mankind. The technological development is applied to the sick people in excessive and unnecessary procedures of vital support for the maintenance of the vital functions, which only achieve in many of the cases to lengthen the patient's agony and the suffering of its relatives. It is understood as a vital ...